Compliance of registered health research ethics committees with South African research ethics guidelines - Molebatsi, Thabo Isaac (University of Limpopo ( Medunsa Campus ), 2010)
Background The National Health Research Ethics Council (NHREC) of South Africa (SA) is mandated to oversee health research ethics activities within the country. The oversight role is achieved through registration and auditing of Health Research Ethics committees (RECs). This study indicates that 22 RECs are registered with the NHREC. Purpose This study examines compliance levels of registered RECs with the SA DOH national health research ethics guidelines regarding composition and operational procedures as well as highlight commonalities and differences. Methods Secondary data of 22 RECs registered with NHREC were used to examine the level of compliance related to composition and operational procedures disaggregated by REC. Data were processed using Statistical Package for Social Scientists (SPSS). Categories of systematic compliance, non-systematic compliance and non-compliance were used to determine RECs compliance levels with the standards specified in the DOH national ethics guidelines in research. Results Registered RECs in South Africa have an average membership of 16 ranging from 6 to 35. The RECs membership on gender has a 6% marginal difference and is dominated (68%) by scientists or clinicians. Majority (82%) of RECs have lay persons and 77% legal representatives. Eighty six percent of RECs xvi complied with operational procedures as stipulated by DOH national health research ethics guidelines. Conclusions Most RECs in SA registered with NHREC have a functional structure and are well organized. However, RECs demonstrated a non-systematic compliance with composition and procedures of DOH national guidelines. Most RECs based at public hospitals, government department and private organizations experienced high variations. Disparities related to gender, professional identity, legal and lay representations are noticeable and could be easily addressed.
Thesis (MPH)--University of Limpopo, 2010.
Keywords: Research ethics; Ethics committees; Ethics guidelines